X‐ray fluorescence determination of sulfur chemical state in sulfide ores. (22nd September 2016) - Chubarov, Victor; Amosova, Alena; Finkelshtein, Alexander
Abstract : This paper describes the X‐ray fluorescence technique for estimation of the ratio between sulfide and total sulfur in sulfide ores using the influence of sulfur chemical state on positions and intensities of lines (SKα1, 2, SKβ1, 3 ) and satellites (SKβ′, SKα3, 4 ) of the sulfur X‐ray emission spectra measured by the wavelength‐dispersive X‐ray fluorescence spectrometer. The samples to be analyzed were prepared as pressed powder pellets on boric acid substrate. The SKα1, 2 line chemical shift is the most appropriate parameter for sulfur chemical state estimation because spectral lines in this field are intensive and are almost not affected by spectral overlap of lead spectrum lines. The ratios of line intensities SKβ′/SKβ1, 3, SKα3, 4 /SKα1, 2 and SKβ1, 3 /SKα1, 2 were also used as analytical parameters. Forty‐one samples of sulfide ores collected in the Russian Far East and Southern Ural deposits have been analyzed. The results of estimation of sulfur chemical state by gravimetric and proposed X‐ray fluorescence techniques agree fairly well. Copyright © 2016 John Wiley & Sons, Ltd.